Rare filamin C variants among patients with hypertrophic cardiomyopathy referred for septal myectomy - S. E. Andreeva; A. V. Gurshchenkov; V. V. Zajcev; A. A. Kozyreva; A. I. Mihaleva; A. S. Murav'ev; V. K. Grebennik; L. B. Mitrofanova; M. L. Gordeev; O. M. Moiseeva; A. A. Kostareva (Российский кардиологический журнал)
Aim. To determine the prevalence and profile of rare variants of the filamin C gene (FLNC) among patients with hypertrophic obstructive cardiomyopathy (HCM) referred for septal myectomy, and to provide a clinical description of HCM occurring with these variants.Material and methods. Ninety-eight adult patients with HCM who underwent septal myectomy underwent genetic testing by next-generation sequencing using a targeted cardiac panel (39-gene panel in 58 patients and 17-gene panel in 40 patients). In patients with rare FLNC variants (with a minor allele frequency <0,01%), the data of anamnesis, echocardiography, electrocardiography, Holter monitoring, and myocardial histological examination were analyzed.Results. Four patients with rare FLNC variants (two men and two women) were identified, which amounted to 4% (Pro1774Ser, Thr1317Pro and His1834Tyr, the latter was detected twice). These variants were missenses and classified as variants of uncertain clinical significance. The FLNC p.Thr1317Pro variant in one patient was combined with a pathogenic variant p.Val606Leu in MYH7 gene. All patients received diagnosis of HCM after age of 40 years. Clinical course was represented by mild symptoms of heart failure and class II stable angina. Episodes of non-sustained ventricular tachycardia, atrial fibrillation or clinically significant conduction block were not registered. One patient with p.His1834Tyr FLNC variant had reverse curve interventricular septum morphology, whereas other patients had predominant hypertrophy of basal segment of interventricular septum. Diastolic dysfunction did not exceed grade 1-2 in all four patients.Conclusion. The clinical characteristics of carriers of rare FLNC variants in our study did not differ from the majority of patients with HCM who underwent septal myectomy. Rare FLNC variants can act as causative or modifying factors of HCM course. Functional and population-based studies using segregation analysis should clarify the pathogenicity of rare FLNC variants.